Investigating the effects of phytohormones on growth and β-carotene production in a naturally isolates stain of Dunaliella salina - Pegah Mousavi, Mohammad Hossein Morowvat, Nima Montazeri-Najafabady, Zohreh Abolhassanzadeh, Abdolali Mohagheghzadeh, Mehrdad Hamidi, Ali Niazi, Younes Ghasemi (Journal of Applied Pharmaceutical Science, 2016)
The algae of the genus Dunaliella especially D. salina is among the microalgae most studied for mass culture. This alga is the richest algal source of glycerol and β-carotene, which is grown as a food source in aquaculture. In this study the effect of growth regulators (kinetin, gibberellic acid, indole-3-acetic acid, 6γ, γ-dimethylallyl aminopurine, salicylic acid and benzyl aminopurine) on the growth and β-carotene production in D. salina (MCCS 001) was investigated. Results pointed out that the β-carotene content and cell growth of D. salina could achieve the highest rates when kinetin and indole-3-acetic acid were used at 1 µM. Besides, it was shown that almost all of plant hormones has a positive effect on cell growth and β-carotene production in the microalga D. salina.
Keywords: Dunaliella salina, Growth rate, Plant growth regulators,β-carotene.